Portrait of an ethnography during pandemic times: Bagamoyo remote reconstruction and the (Un)Freire of literacy policies in Mozambique - Carvalho, X. (VIII Congresso da Associação Portuguesa de Antropologia (APA), 2022)
Remote reconstruction of the beginning of the literacy policies developed by the Frelimo School in Bagamoyo (1970-1975), Tanzania, ending in the first National Literacy Seminar in 1975, in Mozambique, is the ethnography I develop since 2019. I went to the field supported by my previous ethnographic fieldwork (2011-2016), in which the encounter between national languages and the official language became one of the central issues to understand the (re)construction of national identity, looking for the origin of that (re)construction legitimated through the diffusion of the official language. Taking this on board, Paulo Freire (1921-1997), that contributed for the development of critical pedagogy, was a key actor in the development of literacy policies in PALOP post-independence contexts. In Mozambique, the field brought me the other side of the (hi)story, the (Un)Freire (hi)story. During pandemic times, my ethnography is done remotely, supported by a network of shared contacts, tuned with my long personal journey of research and experience in Mozambique. This will not be my final ethnography of Bagamoyo, but the one that the pandemic times allow me at the moment, applying an epistemology based on resilience and methodological resistances that underpinned my practice as an anthropologist. (In VIII Congresso da APA, painel 091 - "Resilience and methodological resistances: ethnographies of Mozambique during pandemic times")